LEFT DISLOCATION IN NEAR-NATIVE FRENCH - Donaldson, Bryan (Studies in second language acquisition, 2011)
The present study is concerned with the upper limits of SLA—specifically, mastery of the syntax-discourse interface in successful endstate learners of second-language (L2) French (near-native speakers). Left dislocation (LD) is a syntactic means of structuring spoken French discourse by marking topic. Its use requires speakers to coordinate syntactic and pragmatic or discursive knowledge, an interface at which L2 learners have been shown to encounter difficulties (e.g., Sorace, 1993; Sorace & Filiaci, 2006). The data come from (a) an 8.5-hr corpus that consists of recordings of 10 dyadic conversations between near-native and native speakers of French and (b) two contextualized paper and audio tasks that tested intuitions and preferences regarding LD. Analyses of the near-native speakers’ production of LDs, the syntactic properties of their LDs, and their use of LDs to promote different types of discourse referents to topic status suggest that their mastery of this aspect of discourse organization converges on that of native speakers.